Early Buddhism as philosophy of existence : freedom and death - Babbitt, Susan E. (Anthem Press, 2022)
"This book makes the connection between early Buddhism and nature. Early Buddhism was a system of thinking which applied the universal laws of nature to human beings. It was not a religion. It was a comprehensive worldview. But after the first 400-500 years, it was slowly lost"--